USP15-USP7 Axis and UBE2T Differential Expression May Predict Pathogenesis and Poor Prognosis in De Novo Myelodysplastic Neoplasm - de Carvalho, Luiz Gustavo Almeida; Komoto, Tatiana Takahasi; Moreno, Daniel Antunes; Goes, João Vitor Caetano; de Oliveira, Roberta Taiane Germano; de Lima Melo, Mayara Magna; Roa, Mariela Estefany Gislene Vera; Gonçalves, Paola Gyuliane [UNESP]; Montefusco-Pereira, Carlos Victor; Pinheiro, Ronald Feitosa; Ribeiro Junior, Howard Lopes (MDPI, 2023)
The aim of this study was to evaluate the expression of USP7, USP15, UBE2O, and UBE2T genes in Myelodysplastic neoplasm (MDS) to identify possible targets of ubiquitination and deubiquitination in MDS pathobiology. To achieve this, eight datasets from the Gene Expression Omnibus (GEO) database were integrated, and the expression relationship of these genes was analyzed in 1092 MDS patients and healthy controls. Our results showed that UBE2O, UBE2T, and USP7 were upregulated in MDS patients compared with healthy individuals, but only in mononucleated cells collected from bone marrow samples (p < 0.001). In contrast, only the USP15 gene showed a downregulated expression compared with healthy individuals (p = 0.03). Additionally, the upregulation of UBE2T expression was identified in MDS patients with chromosomal abnormalities compared with patients with normal karyotypes (p = 0.0321), and the downregulation of UBE2T expression was associated with MDS hypoplastic patients (p = 0.033). Finally, the USP7 and USP15 genes were strongly correlated with MDS (r = 0.82; r2 = 0.67; p < 0.0001). These findings suggest that the differential expression of the USP15-USP7 axis and UBE2T may play an important role in controlling genomic instability and the chromosomal abnormalities that are a striking characteristic of MDS.
Keywords: deubiquitination; gene expression; myelodysplastic neoplasm; ubiquitination